A Study to Assess the Risk Factor of Diabetic Foot Ulcer among Diabetes Mellitus People Residing at Urban Population in Maraimalainagar, Kancheepuram District (Indian Journal of Public Health Research & Development, 2020)
Objectives : The objectives of the study were 1.To assess the risk factors of Diabetic foot ulcer.2.To Findthe associations between risk factors and Diabetic foot ulcer.3.To stratify the foot ulcer risk populationamong diabetes mellitus patients. Method: A Non-experimental descriptive research design was used inthis study.133 clients were selected and explained the purpose of the study and consent was taken. Theclients were interviewed by using questionnaires’ regarding risk factors of diabetic foot ulcer. Client whowere interviewed through the questions were explained by the translator and the answers were markedimmediately. The average time spend for every client is 15 minutes. Result: The result revealed that outof 133 samples 32% of 43 no. of diabetes mellitus people have inadequate knowledge , 61% of 81 no .ofdiabetes mellitus people have moderately adequate knowledge , 6.8% of 9 no. of diabetes mellitus peoplehave adequate knowledge.
Keywords: Assess, risk factor, diabetic foot ulcer, diabetes, clients